Filsafat nilai Max Scheler Nilai dalam Pandangan Perempuan Batak tentang Perniagaan di Pasar Sambu Medan ditinjau dari Perspektif Max Scheller: Values ​​in Batak Women's Views of Business in the Sambu Market in Medan from Max Scheller's Perspective - Putri, Nindya Vera; Sahfutra, Suryo Adi (Jurnal Filsafat Indonesia, 2024)
This paper discusses the meaning of trading for women in the Batak tribe, who make up the majority of traders in the Sambu Medan market area. This study aims to explore why women in the Batak tribe are the most traders in the Sambu Medan market area, isn't it basically the men who have the most role in fulfilling the family's economy? What reason makes them so happy to be a Merchant in the market? These answers will then be examined using the viewpoint expressed by Max Scheler Philosophy of Values. Qualitative research methodology is imployed using primary and secondary data sources. The stages of value contained according to Max Scheler, the following are : first, the worth of pleasure is drawn from their happiness when their wares are selling well so that they get big profits to be used for the smooth running of their family's their children’s education and the economy. Second, the value of life, trading is a necessity of life not only for them personally but also for family life, and there is a very noble purpose of life for survival which is not only for now but for the life to coe, Third, Spiritual/psychological value, Trading is a spiritual need for Batak women whmo are in the Sambu market so they consider trading as an alternative to relieve boredom, peace of mind, happiness and relieve stress in their minds. Fourth, their spiritual values believe that every human being who tries and prays to hope for sustenance from God will get blessings from God.